1994
DOI: 10.1007/bf00187077
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cotrel-Dubousset pedicle screws and hooks in the treatment of idiopathic scoliosis

Abstract: Eighty-two patients with idiopathic scoliosis were treated by Cotrel-Dubousset instrumentation between 1987 and 1991. Twenty were treated with hooks only, 47 with screws and hooks, and 15 with screws only. The methods were compared and the findings showed that screw fixation can be used in the thoracic spine without neurological complications. The screws provided immediate stability with rigid fixation, together with better correction of frontal, sagittal and rotational deformity. There is less loss of correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
126
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(132 citation statements)
references
References 9 publications
3
126
0
3
Order By: Relevance
“…Transpedicular stabilization has become an established method for instrumentation of the thoracic and lumbar spine because of its immediate rigidity, better coronal and sagittal correction and shorter fusion length in scoliosis surgery when compared to the other instrumentation techniques [1,39]. Pedicle screw fixation of the thoracic spine is technically difficult with a high risk of potential complications such as neurologic, vascular and visceral injuries, associated with misplaced pedicle screws [7,8,12,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transpedicular stabilization has become an established method for instrumentation of the thoracic and lumbar spine because of its immediate rigidity, better coronal and sagittal correction and shorter fusion length in scoliosis surgery when compared to the other instrumentation techniques [1,39]. Pedicle screw fixation of the thoracic spine is technically difficult with a high risk of potential complications such as neurologic, vascular and visceral injuries, associated with misplaced pedicle screws [7,8,12,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The initial use of pedicle screws began in the lumbar spine and as surgeons became more comfortable with the complex anatomy required for accurate screw placement, they evolved the use of pedicle instrumentation in thoracolumbar and thoracic spine [23,24,31]. Transpedicular screw fixation has many advantages over other spinal instrumentations such as Harrington rod fixation, Luque's instrumentation, etc., in various pathologies [1,27,31,39,45]. Pedicle screws also prevent the need to place instrumentation within the spinal canal like sublaminar wiring [6], which creates the risk of neurological injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implantation of pedicle screws with spinal instrumentation has shown to have improved coronal, sagittal and rotational deformity correction [2]. Because of the unique neurologic and vascular anatomy of the spinal canal and thoracic cavity, optimal screw placement is especially important for thoracic pedicle screws.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have demonstrated that pedicle screws are superior for correcting scoliosis, in terms of the mean absolute degrees and percentage of curve correction, in comparison with posterior hook-and-wire or hybrid constructs [9][10][11]. Among the several surgical techniques available, pedicle screw instrumentation is considered to be reliable and safe [12][13][14], but clinical trials have reported a lordogenic effect with this form of posterior instrumentation [15][16][17].…”
Section: Introductionmentioning
confidence: 99%